Perbedaan Perkembangan Bicara pada Bayi Usia 2-4 Tahun yang Diberi ASI dan Non ASI di PAUD Nur Hidayah Surakarta - Supu, Siti Mahriwati, Agus Widodo, S.Fis, M.Kes (2017)
Background:Breastfeeding is beneficial to infant growth, especially in the development of baby talk, because breast milk contains all the necessary nutrients in the right amounts, containing antibodies or antibody. This study aims to determine differences in speech development in infants aged 2-4 years who were breastfed and non-breastfed Research Objective:To determine differences in speech development of infants aged 2-4 years who were breastfed and non-breastfed Research Method:Descriptive study is cross-sectional, with purposive sampling method. Data were analyzed using analysis Test Chy Square.Subjek study 60 children aged 2-4 years in early childhood Nur Hidayah Surakarta. The research instrument is a screening tool used ELM-2 scale, a questionnaire to guardians. Result: the results of data processing using Chy Square Test, the results obtained p-value of 0.000 where p <0.05, Ha accepted Conclusion: There are differences in speech development in infants fed breast milk is better than speech development babies are not breastfed.